Integrating Information and Communication Technology Use and Environmental Conservation in Livelihoods of Small Scale Dairy Farmers of Nandi and Uasin Gishu Counties - Beru, M. K.; Kiptui, M.; Cheserek, G. (Africa Environmental Review Journal, 2018)
Dairy farming if not well managed can lead to soil erosion, rise in livestock- human diseases, overgrazing, encroachment into other land uses and negative impact on people’s livelihoods. This adverse effect of dairy farming livelihoods on the environment if not checked, may lead to environmental degradation which, will eventually lead to unsustainable livelihoods and food insecurity. Information and communication Technology (ICT) can be used to reduce such negative environmental impact. The small land holdings and fragmentation characterizing most farms in rural areas poses a challenge to dairy farming. It means the dairy farmers will have inadequate access to resources necessary to adequately practice dairy farming. In addition, small holdings may also pose environmental challenges to dairy farming. It will give a small room for sustainable farming system and a challenge in waste management. The objectives of this study were to assess the nature of environmental conservation information received by small scale dairy farmers via ICT gadgets and to examine the effect of environmental conservation information received on livelihoods of small scale dairy farmers. Findings showed that farmers sort information on proper dairy farming methods and environmental conservation. There is therefore need for small scale dairy farmers to be equipped with adequate knowledge on environmental conservation so as to maintain sustainable dairy farming livelihoods.